(untitled) (Journal of Organizational Psychology, 2022)
The knowledge-based view of the firm has gained currency in organizational theory since the 1990s. This paper evaluates it in a historical perspective, and suggests that the new theories of the firm as a receptacle of knowledge emerged in the context of the intensified knowledge communication within organizations in the early 1990s, and organizational practices that appropriated public property through the regime of intellectual property rights. This paper contends that organizational theory and practice are both in a state of dynamic mutual interaction, with theory often playing a lagging role. In other words, organizational actions precede, and are retroactively described (and legitimized) by theoretical developments. This paper subjects knowledge-based theories of the firm to scrutiny, and concludes that they resort to simplistic definitions of knowledge. Using information from other social sciences, this paper identifies some of the facets of knowledge that need to be considered in order to make the theories posited more meaningful.